Wettability - Donaldson, Erle C. (Gulf Pub. Co., 2008)
The wettability of oil reservoirs is the most important factor controlling the rate of oil recovery, providing a profound effect on petroleum production. The petroleum industry has increased the research effort on wettability, but, so far, there has never been a comprehensive book on the topic. This is the first book to go through all of the major research and applications on wettability, capillary pressure and improved recovery. Critical topics including core preservation, the effect of wettability on relative permeability, surface forces such as van der Waals equation of state, petroleum traps and pore size effects are all included in this musthave handbook. Deciphering the techniques and examples will increase the efficiency and production of oil recovery, translating to stronger reservoir simulations and improved well production.
Keywords: Wetting.; elektronické knihy; electronic books